STRATEGIES ADOPTED TO REDUCE PATIENTS ABANDONMENT TO TREAT TUBERCULOSIS: STRATEGIES ADOPTED TO REDUCE PATIENTS ABANDONMENT TO TREAT TUBERCULOSIS - Celeste, Hozanna Estrela; Souza, Anne Caroline de; Oliveira, Geane Silva; Alencar Neta, Raimunda Leite de; Feitosa, Ankilma do Nascimento Andrade; Silva, Talina Carla da (Brazilian Journal of Production Engineering, 2020)
Objective: To identify through the literature the strategies adopted to reduce the abandonment of tuberculosis treatment. Method: Integrative literature review conducted from April to August 2020, using the databases: LILACS and SCIELO. The studies were selected from the crossing of the descriptors: Tuberculosis. Strategy. Abandonment. Treatment. The guiding question used was: What strategies can be adopted to reduce patient abandonment during tuberculosis treatment? The inclusion criteria listed in this review were: articles published in English and Portuguese; full text available online, free access, which were dated from 2016 to 2020 and permeated the topic discussed. Results: When crossing the descriptors, it was possible to locate 34 articles in the two databases, of these 27 in Scielo and 07 in LILACS. Upon careful reading of the articles, 06 publications from different journals were selected to compose the integrative review, since they met all the inclusion criteria inherent to the present study. Conclusion: The study concludes that the publications listed were relevant to the context in which they were intended to work, since, despite being mostly recent published after 2019, it is noted that many strategies can be implemented in the treatment of tuberculosis aiming at greater adherence of patients, allowing them to develop a bond with the health team and to have greater autonomy throughout the TB cure process.